2021
DOI: 10.1016/j.chemosphere.2020.128445
|View full text |Cite|
|
Sign up to set email alerts
|

Detrimental effect of Bisphenol S in mouse germ cell cyst breakdown and primordial follicle assembly

Abstract: Bisphenol S (BPS) exposure results in abnormal germ cell cyst breakdown. BPS exposure activates the JNKs signaling through estrogen receptors. BPS exposure increase the proliferation of granulosa cells precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…At this point, there are still plenty of oocytes remaining in the ovarian cysts. Consistent with previous studies Liu et al, 2019;Liu W. X. et al, 2021;Tian et al, 2021;Wang et al, 2021), the effect of the drug on germ cell cyst breakdown and PF formation could be measured by counting the proportion of oocytes in cysts and follicles. In addition, newborn mice were fed normally after 4 days of intraperitoneal injection.…”
Section: Animals and Reagentssupporting
confidence: 58%
See 1 more Smart Citation
“…At this point, there are still plenty of oocytes remaining in the ovarian cysts. Consistent with previous studies Liu et al, 2019;Liu W. X. et al, 2021;Tian et al, 2021;Wang et al, 2021), the effect of the drug on germ cell cyst breakdown and PF formation could be measured by counting the proportion of oocytes in cysts and follicles. In addition, newborn mice were fed normally after 4 days of intraperitoneal injection.…”
Section: Animals and Reagentssupporting
confidence: 58%
“…As previously described ( Liu W. X. et al, 2021 ), the rehydrated sections were antigen retrieved with sodium citrate and treated in 3% H 2 O 2 for 10 min. Next, sections were blocked with BDT and incubated with primary antibodies ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…BPAF compromises blood‐testis barrier integrity and sperm quality in mice, 35 and disrupts oocytes maturation in mouse in vitro through increasing oxidative stress and DNA damage 36 . BPS induces an abnormal germ cell cyst breakdown and primordial follicle assembly, affecting oocytes quality and meiotic maturation in mice 37 . BHPF, as well as BPB, was also confirmed to cause damage to female reproduction and deteriorates oocytes potential 30,31 .…”
Section: Discussionmentioning
confidence: 89%
“…36 BPS induces an abnormal germ cell cyst breakdown and primordial follicle assembly, affecting oocytes quality and meiotic maturation in mice. 37 BHPF, as well as BPB, was also confirmed to cause damage to female reproduction and deteriorates oocytes potential. 30,31 BPF, the most common bisphenol, is inevitable in daily human life.…”
Section: Comparison Of the Effects Of Bpf And Bpa On Dna Damage And O...mentioning
confidence: 92%
“…Owing to the similarity of its chemical structure with endogenous estrogen (17β-estradiol; E 2 ), the toxicity of ZEA on the female reproductive system has received widespread attention [17][18][19][20]. Relevant to the present work, some papers show that the drugs can impair PF formation [21][22][23]. Other researches have reported that PF formation can be inhibited by exposure to environmental estrogens and high concentrations of E 2 , and ZEA exposure signi cantly inhibit PF formation in embryonic stage E17.5 or postnatal 0 day (PD0) mouse ovaries [24,25].…”
Section: Introductionmentioning
confidence: 80%